Pediatric paraneoplastic neuromyelitis optica spectrum disorder associated with ovarian teratoma. (January 2022) - Tardo, Lauren; Wang, Cynthia; Rajaram, Veena; Greenberg, Benjamin M
Neuromyelitis optica spectrum disorder is an inflammatory condition of the central nervous system typically manifesting as myelitis, optic neuritis, and/or area postrema syndrome. Here, we present a pediatric patient who developed symptoms consistent with area postrema syndrome with positive anti-aquaporin-4 (AQP4) antibodies who was also found to have an ovarian teratoma. Pathological specimens revealed the presence of aquaporin-4. This was felt to be the antigenic trigger that led to the patient's condition. She suffered no further clinical attacks and seroconverted to negative AQP4 status upon teratoma removal. This case varies from others, in that the paraneoplastic presentation occurred in a pediatric patient and in that the patient has not required maintenance immunotherapy after teratoma removal.